Aerodynamic modeling methods for a large-scale vertical axis wind turbine: A comparative study. (December 2018) - Hand, Brian; Cashman, Andrew
Abstract: Vertical axis wind turbines (VAWTs) are experiencing a renewed interest for large-scale offshore wind energy generation. However, the three-dimensional (3D) modeling of VAWT aerodynamics is a challenging task using computational fluid dynamics (CFD), owing to the high computational costs entailed. To alleviate this computational burden and improve design process efficiency, an alternative low-order model (LOM) is presented that incorporates key VAWT aerodynamic effects. These coupled sub-models account for the influence of dynamic stall, tower shadow, parasitic drag, flow curvature and finite blade effects. A two-step approach is adopted to investigate two-dimensional (2D) and 3D VAWT aerodynamics separately with experimental data. A CFD model was created and both modeling strategies were compared. The LOM showed good agreement with the CFD model and the measurements with a low computational cost requirement. The CFD results identified that as the tip-speed ratio (TSR) was increased, the tower's downwind wake became increasingly more skewed. Finally, both the LOM and the CFD model were employed in predicting the VAWT aerodynamic efficiency. It was established 3D effects must be included to provide an accurate prediction of VAWT performance especially at high TSRs. For VAWT analysts, modeling recommendations and limitations are discussed regarding the LOM. Highlights: Low-order model for large-scale VAWT aerodynamic conceptual design is presented. Modelling of 2D and 3D aerodynamics are studied with large-scale experimental data. LOM is compared with 2D CFD model and predicts performance with lower CPU demand. CFD shows rotating tower produces skewed von Kármán vortex street wake formation. Inclusion of 3D effects provides reliable LOM efficiency predictions at high TSRs.